Chasing rainbows online news empowerment framing of L.G.B.T.'s social and political conditions - Arabelo, Leslie Ann Sto. Domingo; Merida, Maxlee Y. (2013)
"The lesbians, gays, bisexuals, and transgenders/transsexuals (L.G.B.T) are often socially and politically marginalized because of their deviation from what is considered normal by heteronormative society. The media, known as powerful tools in shaping perceptions and effecting change, take on a crucial role in framing the empowerment of this marginalized group through the news that it published. Thus, this thesis examined how empowerment of the L.G.B.T's social and political conditions is framed in three online news websites namely the Manila Bulleting, the Philippine Daily Inquirer and the Philippine Star. Furthermore, it seeks to determine whether the socio-political conditions and empowerment reflected in the news are congruent to the reality experience by the L.G.B.T.s. The Queer theory, Loevinger's Projective-Reflective Theory, and the World Bank's Empowerment Model served as theoretical foundations of this research. Ten months' worth of news articles mentioning L.G.B.T.s were content analyzed and focus interviews were conducted with 12 L.G.B.T informants. Results showed that the three news websites publish mostly anti-heteronormative news articles. Despite this, low over-all empowerment from the three news sites was observed. Manila Bulletin was found to be the least socially empowering and Philippine Star as the least politically empowering. Generally, incongruence was noticed between the empowerment in news and empowerment expressed by the informants. However, empowerment shown by the news in terms of certain indicators such as health, civil and political rights, human rights were congruent with reality. The incongruence, as a result, may establish a false belief among the general audience which can ultimately affect their perception, attitude and behavior towards the L.G.B.T."